E-health and its Impact on Indian Health Care: An Analysis. Issue 2 (December 2019) - Kaur, Sukhpreet; Kaur, Rajinder; Aggarwal, Rashmi
Healthcare sector is progressing towards digitalization in every aspect such as e-consultations, health surveillance, health education and various other healthcare services. Developing countries like India lacks infrastructure to conduct studies to evaluate impact of these e-health services on patient outcomes. Various developed countries have electronic health records which makes evaluation of patient outcomes much easier. This paper aims to evaluate effect of e-health on patient outcomes in Indian healthcare scenario and future consequences of these e-health services. The integrative literature searches were conducted using various databases such as pubmed, google scholar and SCC web edition using keywords such as 'e-health', 'telemedicine', 'mhealth', 'electronic health records', 'patient outcomes' and 'data protection laws'. From the papers retrieved only few papers studied impact of e health services in patient outcomes. Other papers assessed e-health on basis of accessibility, feasibility and medium of education in clinical practice. It was concluded that e-health services such as diagnostic services like teleopthalmology and tele ECG, distant consultation with specialist through telemedicine and adherence aids like automated voice reminder and pictorial messaging have positive impact on patient outcomes. Though e-health services can help us in various ways but it will also open the new Pandora box of problems in handling personal information. The information technology rules in India have certain grey areas in protection of digital data. In future, besides improving the data content of information system to analyse the impact of various services provided to the patients, we will have to relook the legal system to protect the data.